TINGKAT KESESUAIAN SOAL TEORI UJI KOMPETENSI KEAHLIAN TEKNIK GAMBAR BANGUNAN DENGAN STANDAR KOMPETENSI NASIONAL BIDANG GAMBAR BANGUNAN - Abdul Malik (Jurnal Pendidikan Teknik Sipil, 2019)
ABSTRACT                Phenomena that show the competence of building drawings that are needed in the world of work but have not been studied in schools are the basis of research. It is necessary to measure the level of compatability between the materials being studied with the competencies required by the world of work. The purpose of this study was to determine the suitability level of the content of the skills competency test (UKK) based on the National Competency Standars in the Building Drawing Field. The research method used is comparative descriptive. The subject of this research is the matter of the theory of UKK Building Drawing Engineering. Data were analyzed by comparing the level of competency suitability implemented in the UKK theory problem with the National Competency Standards in Building Drawing Field. The results of the study showed that in the implementation of the UKK Building Drawing Tecnique in theory there were 37 competencies tested. Total competencies at the level of young photographers for vocational graduates are 55 competencies. There are 18 competencies that have not been tested on UKK, so there needs to be an adjustment so that the UKK content goes hand in hand with the work competencies required for building drawing skills. Keywords: expertise competency test, building drawing  ABSTRAK                Fenomena menunjukkan adanya kompetensi gambar bangunan yang diperlukan di dunia kerja tetapi belum dipelajari di Sekolah menjadi dasar dalam pengkajian. Perlu adanya pengukuran tingkat kesesuaian antara materi yang dipelajari dengan kompetensi yang disyaratkan dunia kerja. Tujuan dari pengkajian ini adalah mengetahui tingkat kesesuaian antara konten soal Uji Kompetensi Keahlian (UKK) mengacu pada Standar Kompetensi Nasional Bidang Gambar Bangunan. Metode pengkajian yang digunakan adalah deskriptif  komparatif. Subjek pada pengkajian ini adalah soal teori UKK Teknik Gambar Bangunan. Data dianalisis dengan membandingkan antara tingkat kesesuaian kompetensi yang dilaksanakan dalam soal teori UKK dengan Standar Kompetensi Nasional Bidang Gambar Bangunan. Hasil pengkajian menunjukkan dalam pelaksanaan UKK Teknik Gambar Bangunan secara teori terdapat 37 kompetensi yang diujikan. Total kompetensi pada level juru gambar muda untuk lulus SMK adalah 55 kompetensi. Terdapat 18 kompetensi yang belum diujikan pada UKK, sehingga perlu adanya penyesuaian agar konten UKK beriringan dengan kompetensi kerja yang disyaratkan pada keahlian gambar bangunan.Kata Kunci: Uji Kompetensi Keahlian, gambar bangunan